PREDICTORS OF ARTERIAL HYPERTENSION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS IN AZERBAIJAN POPULATION - S. Kh. Mekhdiyev; I. I. Mustafaev; M. N. Mamedov (Российский кардиологический журнал)
The presented study in Azerbaijan is carried out for the first time within State Programs on fight against a type 2 diabetes mellitus (DM2) and other noninfectious diseases.Aim. To define predictors of arterial hypertension (AH) in patients with DM2 in Azerbaijan population.Material and methods. In the single-step clinical-epidemiology cohort study were included 528 patients with DM2 at the age of 30-69 (30,5% — men and 69,5% — women) who answered questions using “ARIC” questioner to define AH and its risk factors.Results. The prevalence of AH in women (72,4%) was 2,6 times more than in men (27,6%) and the frequent occurrence of AH was at the age of 60-69 (respectively, 26,7±2,1% vs 9,6±2,9%, p<0,001). It was not determined remarkable differences between AH level and occupation status, alcohol consumption, low physical activity, feeding disorder of the patients, at the same time in patients with AH smoking frequency was about 2 times often than in others (respectively, 19,3±1,9% vs 10,6±3,0%, p<0,05). In parents of AH patients AH rates, in comparison with eutonics, were occurred like these: (respectively, in fathers 21,9±2,0% vs 12,5±3,2%, p<0,05; in mothers 42,2±2,4% vs 26,9±4,3%, p<0,01), in mothers DM2 (respectively, 33,7±2,3% vs 221 ±4,1 %, p<0,05), overweight and obesity were watched much more often (95,0±1,1% vs 88,5±3,1%, p<0,05), at the same time these patients were suffered from abdominal obesity (respectively, 96,5±0,9% vs 89,4±3,0%, p<0,01). The mean values of systolic and diastolic arterial pressure (respectively, 148,3±1,1 vs 119,8±1,3 Hg, p<0,001 and 85,9±0,5 vs 74,8±0,8 Hg, p<0,001) were often determined in patients with AH, and on the other hand in these patients were noted prevalence of anxious syndrome (respectively, 78,5±2,0% vs 72,1±4,4%, p<0,05) and depression (68,2±2,3% vs 62,5±4,7%, p>0,05). Regardless of AH level in all patients was noted stress (respectively, 99,8±0,2% vs 100,0±0,0%, p>0,05), which changed for the worse life quality of the patients with AH significantly (respectively, 1,0±2,2% vs 61,5±4,8%, p<0,05).Conclusion. For patients with DM2 in Azerbaijan cohort female sex, increasing of the age, body mass index, abdominal obesity and anxious conditions are significant risk factors for AH. Presence of AH in both parents and DM2 in mothers increase this risk significantly, which decrease life quality of these patients.